2013
DOI: 10.4049/jimmunol.1203484
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Unresponsiveness of Chronic Lymphocytic Leukemia Cells Results from Impaired Endosomal Recycling of Rap1 and Is Associated with a Distinctive Type of Immunological Anergy

Abstract: Trafficking of malignant lymphocytes is fundamental to the biology of chronic lymphocytic leukemia (CLL). Transendothelial migration (TEM) of normal lymphocytes into lymph nodes requires the chemokine-induced activation of Rap1 and αLβ2 integrin. However, in most cases of CLL, Rap1 is refractory to chemokine stimulation, resulting in failed αLβ2 activation and TEM unless α4β1 is coexpressed. In this study, we show that the inability of CXCL12 to induce Rap1 GTP loading in CLL cells results from failure of Rap1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Impaired chemokine responsiveness in CLL cells is likely due to a failure of Rap1-containing endosomes to translocate to the plasma membrane, resulting in defective in Rap1 GTP-loading. 30,31 It is possible that overexpression of CALDAG-GEFI, RAP1B, and RAPL in trisomy 12 CLL cells may compensate for this defect and further improve function, and this will be the focus of future experiments. The mechanisms underlying upregulation of integrin signaling in trisomy 12 remain unclear, although a recent report has implicated altered epigenetic regulation as a cause of increased CD49d expression.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired chemokine responsiveness in CLL cells is likely due to a failure of Rap1-containing endosomes to translocate to the plasma membrane, resulting in defective in Rap1 GTP-loading. 30,31 It is possible that overexpression of CALDAG-GEFI, RAP1B, and RAPL in trisomy 12 CLL cells may compensate for this defect and further improve function, and this will be the focus of future experiments. The mechanisms underlying upregulation of integrin signaling in trisomy 12 remain unclear, although a recent report has implicated altered epigenetic regulation as a cause of increased CD49d expression.…”
Section: Discussionmentioning
confidence: 99%
“…For CXCR4, it has been proposed that impaired endosomal recycling of Rap1 is important. 61 In addition to these studies which potentially reveal a trans-inhibitory effect of prior antigen engagement in vivo, other modes of BCR crosstalk have been demonstrated following sIgM engagement in vitro with clear effects on the expression and function of the chemokine receptor CXCR4 and the adhesion molecule CD49d. [72][73][74] For CXCR4, sIgM engagement has been shown to reduce expression of CXCR4 but can either enhance or decrease CXCL12-dependent migration.…”
Section: Effects Of Bcr-mediated Signaling On Remote Receptors In Cllmentioning
confidence: 99%
“…Furthermore, it was reported that defective chemokine-induced Rap1 activation may be linked to impaired motility in a subset of primary CLL cells. 47 Therefore, the fact that we have functionally linked CD38 expression and Rap1 activity is particularly relevant in CLL pathology.…”
Section: Discussionmentioning
confidence: 99%